Tinjauan tentang Subjek Hukum Korporasi dan Formulasi Pertanggungjawaban dalam Tindak Pidana - Paulus Aluk Fajar Dwi Santo (Humaniora, 2012)
Article clarified corporate application as a law subject that had not been fully applied in Indonesia. Corporate status as a subject for criminal law only could be found in Criminal Law Legislation, out of KUHP that had been categorized as special criminal law, or administrative regulation having crime sanction.  The research applied yuridis –normatif and yuridis comparative methods with the following results. There is incompleteness for the status of a corporate, when the corporate will be considered as a liable institution, how to show the liability, etc. The corporate liability in Indonesia in the special criminal law ( outside KUHP), started with UU no. 7/Drt/1955  concerning Economy Criminal Act that later was continued by other special  criminal law up to the  affects that the corporate responsibility did not work in general, but  it was only limited and applied to some special regulations out of those KUHP. Therefore, the design of Criminal Law Regulations that will be authorizeed into Law is supposed to be able to be guidance in overcoming   corporate ‘s criminals